The occurrence and distribution of antibiotics in Lake Chaohu, China: Seasonal variation, potential source and risk assessment. (March 2015) - Tang, Jun; Shi, Taozhong; Wu, Xiangwei; Cao, Haiqun; Li, Xuede; Hua, Rimao; Tang, Feng; Yue, Yongde
Highlights: The highest levels of antibiotics were detected in western inflowing rivers of Lake Chaohu. Sewage treatment plants were important source of antibiotics input to river. Seasonal variations and distribution of antibiotics were observed in surface water. Algae and aquatic plants may be at risk of antibiotics in inflowing river and surface water. Abstract: The distribution and seasonal variation of fifteen antibiotics belonging to three classes (sulfonamides, fluoroquinolones and tetracyclines) were investigated in Lake Chaohu, China. The concentrations of the selected antibiotics in the surface water, eight major inflowing rivers and sewage treatment plant (STP) samples were analyzed by UPLC–MS/MS. The results indicated that sulfamethoxazole and ofloxacin were the predominant antibiotics, with maximum concentrations of 95.6 and 383.4 ng L −1, respectively, in the river samples. In Lake Chaohu, the western inflowing rivers (the Nanfei and Shiwuli Rivers) were the primary import routes for the antibiotics, and the domestic effluent from four STPs were considered the primary source of the antibiotics. The level of antibiotics in Lake Chaohu clearly varied with seasonal changes, and the highest detectable frequencies and mean concentrations were found during the winter. The quality of water downstream of Lake Chaohu was influenced by the lake, and the results of risk assessment of the antibiotics on aquatic organisms suggested that sulfamethoxazole, ofloxacin, ciprofloxacin and enrofloxacin in the surface water of Lake Chaohu and inflowing rivers might pose a high risk to algae and plants.